Analysis of Factors Causing Moral Degradation of Adolescents in the Perspective of Islamic Education in Langon Village, Tahunan District, Jepara Regency - Ni'mah, Khofifatun; Mufid, Mufid (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This research aims to determine the factors that cause the moral degradation of adolescents in Langon Village, Tahunan District, Jepara Regency. This research used a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. Data sources consisted of adolescents aged 18-23 years in Langon Village, Tahunan District, Jepara Regency. The results of this research show that several factors cause moral degradation in Langon Village, Tahunan District, Jepara Regency (1) The influence of the family (parents) in educating and supervising the behavior of adolescents, families tend to give freedom to adolescents so that adolescents are increasingly uncontrolled to take deviant actions. (2) The influence of the social environment and peers, adolescents pay less attention to who their friends are. They associate with their peers with an important feeling of comfort, fun, excitement, and frequency. Adolescents do not pay attention to the morals of their peers so they are easily influenced, following, and unhealthy social associations. (3) The low emotional intelligence of adolescents so that they cannot control their emotions and are encouraged to do deviant things. (4) Unhealthy use of social media and the impact of spreading negative content that can harm adolescent morality. This research also provides an Islamic education perspective to understand adolescent morals. For example, how should adolescents act according to Islamic teachings to avoid immoral behavior? Keywords: Degradation, Morals, Adolescents